Carbonated dairy beverages: challenges and opportunities - Newbold, Daniel Scott (Kansas State University, 2018)
Yogurt drinks have seen a 66% increase in consumption over the last 5 years. Even though there has been an increase in yogurt drink consumption, the market share of drinkable dairy beverages remains small. Carbonated dairy beverages have become increasingly popular in recent years and innovations in this area could help drive increased consumption of these beverages. Currently traditionally carbonated dairy beverages, like kefir, are the most popular carbonated dairy beverages on the market. Carbonation at appropriate levels in dairy products, especially dairy beverages, has been shown to improve the sensory attributes, quality, and shelf life of these products. Probiotics, which are added to yogurt drinks for their health benefits, are not harmed or negatively affected by carbonation. Several methods have been developed to carbonate dairy beverages in a manufacturing setting, although these methods have not been widely applied to commercially available products. The increased consumption of dairy beverages and the benefits of carbonation upon these beverages means that there are opportunities to develop a widely accepted and popular carbonated dairy beverages. The objective of this article was to review available literature on carbonated dairy beverages and to discuss challenges and opportunities in this area.
Keywords: Carbonated; Beverages; Dairy; Yogurt; Kefir